1977
DOI: 10.1111/j.1463-6395.1977.tb00230.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in the Newt, Trituroides hongkongensis, Testis. I. A Histological and Histochemical Study

Abstract: The testis of the newt, Trituroides hongkongensis is found to be made up of a chain of lobes each being divided into spermatogenetic zones which display seasonal cycles. Seasonal changes in the histology of the testis are studied. Lobule boundary cells are found present at the same time of the year when the secondary sex character, a lateral blue line along the tail, is best expressed. Both 5‐ene‐3β‐ and 17β‐HSD activities have been located in the lobule boundary cells which are suggested to be steroidogenic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
1

Year Published

1978
1978
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 11 publications
1
5
0
1
Order By: Relevance
“…In the present study, using a modified WATTENBERG'S technique, it was clearly demonstrated that (i) the reaction for the test of A5-3P-HSD is negative in the pericystic cells containing spermatogonia and spermatocytes, and Sertoli cells, (ii) a weak reaction is found in pericystic cells containing mature spermatozoa with a tendency for the reaction to be more intense in the cysts situated nearer to the glandular tissue, and (iii) a very strong reaction is found in the cells of the outer layer of glandular tissue which originates from the pericystic cells. These results are in accordance with those found in Pleurodeles waltlii (7,38), Salamandra salamandra (1 0 , 23), Trituroides hongkongensis (43) and Triturus cristatus (15,47). Such unique localization of the SH-secreting cells was also reported in certain kinds of fishes, in which the tubule boundary cells constituting the wall of the seminiferous tubules were suggested to be the source of testicular androgens (29,31).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, using a modified WATTENBERG'S technique, it was clearly demonstrated that (i) the reaction for the test of A5-3P-HSD is negative in the pericystic cells containing spermatogonia and spermatocytes, and Sertoli cells, (ii) a weak reaction is found in pericystic cells containing mature spermatozoa with a tendency for the reaction to be more intense in the cysts situated nearer to the glandular tissue, and (iii) a very strong reaction is found in the cells of the outer layer of glandular tissue which originates from the pericystic cells. These results are in accordance with those found in Pleurodeles waltlii (7,38), Salamandra salamandra (1 0 , 23), Trituroides hongkongensis (43) and Triturus cristatus (15,47). Such unique localization of the SH-secreting cells was also reported in certain kinds of fishes, in which the tubule boundary cells constituting the wall of the seminiferous tubules were suggested to be the source of testicular androgens (29,31).…”
Section: Discussionsupporting
confidence: 91%
“…As a result of this technique, it has been possible to identify the SH-secreting cells in various steroidogenetic tissues in a number of animals (28). In amphibian urodeles, too, several investigators have been engaged in the identification of SH-secreting cells in the testes of Pleurodeles waltlii (7, 38), Salamandra salamandra (23), Trituroides liongkongensis (43) and Triturus cristatus ( 1 5, 47). They have confirmed that A5-3P-HSD is localized in the pericystic cells of glandular tissue and cysts before and after spermiation.…”
mentioning
confidence: 99%
“…13,28,39,34,49,44 The urodele testicular cycle is synthesized in several phases: proliferative phase, characterized by mitotic divisions, when proliferation of spermatogonia forms new cysts where spermatocytes advance in spermatogenesis; meiotic phase, characterized by meiotic divisions, when primary and second spermatocytes are formed and develop spermatids; spermiogenesis phase when spermatids differentiate to spermatozoa; and, spermiation when cysts of spermatozoa open and spermatozoa leave the testicular lobules. After spermiation occurs the development of Leydig cells into glandular tissue.…”
Section: Spermatogenesismentioning
confidence: 99%
“…During the regression period, Leydig cells suffer rapid involution. 28 The morpho-physiological changes of Leydig cells are described in several species: Ambystoma tigrinum 26,28 ; Trituroides hongkongensis 13 ; Cynops pyrrhogaster pyrrhogaster 45 ; A. mexicanum 32,39 ; and Necturus maculosus 31,43 ; Triturus marmoratus.…”
mentioning
confidence: 99%
“…Histochemical, biochemical and ultrastructural investigations have clearly demonstrated that the glandular tissue in the urodelan testis, i.e. in particular those celis which have developed from the fibrocytic lobule boundary of the immature part, synthesize steroid hormones (see, for example, Picheral 1970, Joly 1971, Tso and Lofts 1977a, Imai and Tanaka 1978, Tanaka and Iwasawa 1979, Lazard 1979, Callard et al 1980. Supported by the histochemical findings of Joly (1971), as well as our ultrastructural findings, in S.salamandra, the bulk of steroid hormones appears to be produced in the most caudal part of the testis, the glandular tissue.…”
Section: Discussionmentioning
confidence: 99%